شرحِ حدیث کے قدیم ومعاصر مناہج کا تعارفی مطالعہ: A Study of Classical and Contemporary Methodologies of Hadith Explanation: An Introduction - Hafiz Abdul Rahman Madni; Zia Ur Rehman; Iqra Tahir (International Research Journal of Arabic and Islamic Studies, 2024)
This study provides a comprehensive developmental review of Hadith sciences, focusing specifically on the specialized study of Sharh al-Hadith (exegesis of Hadith). The research delves into the evolution and refinement of Hadith scholarship over time, examining the methodologies, contributions, and significant developments within the field. By exploring historical contexts, scholarly debates, and key figures, the study aims to shed light on the advancements in Hadith sciences and the particular role of Sharh al-Hadith in the broader context of Islamic jurisprudence and theology.